Dopant-induced photodegradation of organic water pollutants using cobalt oxide nanostructures of low cytotoxicity. Issue 2 (April 2023) - Ranjitha, R.; Dileep Kumar, V.G.; Navada, Meghana K.; Shetty, Shivaprasad M.; Jayanna, B.K.; Bhatt, Aarti S.; Santosh, M.S.; Madhyastha, H.; Sakai, K.; Ravikumar, C.R.
Abstract: Metal oxides are the simplest and most approachable solutions for attaining multifunctional properties applicable to modern-day technology. With growing concern over environmental conservation, an evaluation of the cytotoxicity of the metal oxides becomes necessary. The present work focuses on the photocatalytic and cytocompatibility behavior of Co3 O4 nanomaterial. It has been observed that the addition of Li to the Co3 O4 nanostructure generates a positive impact on the photodegradation of cationic dyes under UV light. The photocatalyst with 1 wt% Li-doped Co3 O4 was found to be the most competent among the synthesized samples. Further, the sample has been employed for photocatalytic removal of the hazardous pollutant, pyrocatechol (PyC), in the presence of visible light. A photocatalytic efficiency of 84.5% (after 9 h) and high stability (86% after 5 cycles) is observed. A noteworthy revelation is the lower toxicity observed for Li-doped samples when compared to the pristine Co3 O4 . The (3-(4, 5-dimethylthiazolyl-2)− 2, 5-diphenyltetrazolium bromide) (MTT) assay carried out on mouse skin fibroblast cell lines reveals cytotoxicity inhibition by the doped nanostructures for up to 10 μg mL −1 concentration and excellent cell proliferation up to 24 h. The superior catalytic behavior and non-toxic nature of the Li-doped Co3 O4 nanostructures provide ample opportunity for their integration into water remediation and effluent treatment systems. Graphical Abstract: ga1 Highlights: Removal of toxic organic pollutants from wastewater by advanced oxidation process. Li doped Co3 O4 is an efficient photocatalyst under UV and also visible light. Generation of several reactive OH radicals on Co3 O4 surface. Cytotoxicity evaluation of Li doped Co3 O4 on mouse skin fibroblast cell lines.